Treatment of Pulmonary Exacerbations Improves Short But Not Long-Term Growth Trajectory in Children With Cystic Fibrosis. Issue 4 (October 2016) - Loong, Christine; Breton, Jessica; Yang, Connie L.
Abstract : Supplemental Digital Content is available in the text ABSTRACT: Objectives: The present study sought to determine the long-term growth consequences after a pulmonary exacerbation in children with cystic fibrosis (CF). Methods: Retrospective cohort study of pediatric patients with CF with a hospital admission for a pulmonary exacerbation. Logistic regression used to determine risk factors for failure to recover baseline body mass index (BMI) percentile. Results: Of 72 patients, 43% failed to recover their baseline BMI percentile 12 months after discharge and these patients also had a lower forced expiratory volume in 1 second at follow-up. A greater decrease in weight percentile from baseline to admission was the only risk factor identified (odds ratio 0.83, P  = 0.0015). Conclusions: Greater decrease in weight percentile from baseline to admission predicts failure to recover BMI percentile 1 year after a pulmonary exacerbation. Children with CF with poor growth preceding a pulmonary exacerbation continue to be at risk for long-term nutritional failure despite treatment for pulmonary exacerbation.